Age-specific reference ranges and variation of anti-mülerian hormone in healthy Chinese women of reproductive and perimenopausal age: a nationwide population-based prospective multicenter cross-sectional study - Linli Hu; Hongyi Yang; Haining Luo; Yuexiang Zhang; Xiaohong Wang; Sanhua Wei; Qiongfang Wu; Ying Jiang; Xiaoyan Liang; Jianhui Chen; Yingpu Sun† (Gynecological Endocrinology)
Objective To determine the variation of serum AMH levels in healthy Chinese women and establish AMH reference ranges accordingly.Methods This prospective cross-sectional multicenter study was designed to enroll healthy Chinese women of reproductive age (20–39 years) and perimenopausal age (40–49 years) from five reproductive centers in different regions of China. The study began in May 2022 and finished in February 2023. Age-specific 2.5th–97.5th percentiles AMH reference ranges were established. Multivariable linear regressions were undertaken to analyze the association of serum AMH with different demographic and clinical variables, including antral follicle count (AFC).Results 1113 healthy Chinese women were enrolled, including 614 of premenopausal age and others of reproductive age. The AMH (ng/ml) reference ranges for Chinese women of reproductive age were 0.87–9.89 (20–24 years), 0.42–8.24 (25–29 years), 0.34–7.46 (30–34 years), and 0.28–5.66 (35–39 years). For perimenopausal women, their reference ranges were 0.12–4.63 (40–41 years), 0.01–4.12 (42–43 years), 0.01–2.65 (44–45 years), 0.01–1.90 (46–47 years), and 0.01–1.08 (48–49 years). The regression of AMH on AFC adjusted by age is Log10(AMH)=0.2594–0.0235*Age + 0.0632*AFC.Conclusions This study established the age-specific serum AMH reference ranges for healthy Chinese women of reproductive and premenopausal age, and observed that the consistent decrease of AMH after 20 years accelerated around the beginning of perimenopause (40 years).